2023
DOI: 10.1088/1361-6528/ace913
|View full text |Cite
|
Sign up to set email alerts
|

Recent research trends in textile-based temperature sensors: a mini review

Abstract: In this review, the current state of research on textile-based temperature sensors is explored by focusing on their potential use in various applications. The textile-based sensors show various advantages including flexibility, conformability and seamlessness for the wearer. Integration of the textile-based sensors into clothes or fabric-based products enables continuous and sensitive monitoring of change in temperature, which can be used for various medical and fitness applications. However, there are lacks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…A theoretical model for the wavelength shift of a metal-coated FBG for a temperature sensor is reported in a previous study [35]. Researchers have also reported enhancements in the sensitivity of the sensor using polyimide adhesive coated on FBG [36]. They have shown that sensitivity is nearly equal to that of general FBG for a range of temperature around 250 • C [25,26].…”
Section: Introductionmentioning
confidence: 93%
“…A theoretical model for the wavelength shift of a metal-coated FBG for a temperature sensor is reported in a previous study [35]. Researchers have also reported enhancements in the sensitivity of the sensor using polyimide adhesive coated on FBG [36]. They have shown that sensitivity is nearly equal to that of general FBG for a range of temperature around 250 • C [25,26].…”
Section: Introductionmentioning
confidence: 93%
“…In terms of wearable applications, wearable temperature sensors are developed rapidly because the accurate detection of body temperature is a significant part of human health monitoring. At present, NWs with excellent thermal properties have been used as a kind of sensing material for temperature sensing [131]. In this section, a series of typical NW-based wearable temperature sensors with different mechanisms and materials are introduced briefly.…”
Section: Nw-based Wearable Temperature Sensorsmentioning
confidence: 99%
“…The main substrates are natural materials like pectin or silk, cellulose materials (paper), silicon gels like Ecoflex or PDMS, or polymers such as polyurethane (PU) or polyimide (PI). Particularly for textiles, temperature sensors are enumerated as follows [120]:…”
Section: Healthcarementioning
confidence: 99%